Influence of biometric parameters of fruits of Psidium guajava L. about the infestation indices of fruit flies (Diptera: Tephritidae) (Research, Society and Development, 2020)
The present work aims to understand the influence of the biometric parameters of Psidium guajava L. fruits on the fruit fly infestation rates. The study was conducted between the periods from March 2016 to March 2017, where guava fruits were harvested from different locations in the municipality of Juína, these were taken to the Biological Sciences laboratory of the Institute Federal of Mato Grosso (IFMT), which were weighed in and measured by obtaining the diameter and length measurements, these were relocated from the plastic packaging to a tray that contained sand sterilized at 115 ° C. To obtain the insects, the pupils were removed by sifting the sand weekly in which the fruits remained. After emergence, they were fed with honey for two days and then sacrificed and deposited in glass bottles with 70% alcohol. Pearson's correlation test was performed between the volume and density of the fruits with the number of pupils obtained. The Anastrepha genus presented 95.5% of the total flies, C. capitata represented by 3.9% and 4 parasitoids of the Braconidae family (0.6%). Of the recovered individuals, A. striata presented (39.65%) while A. obliqua obtained (7.28%), and C. capitata presented (4%). The fruit fly infestation rate in Psidium guajava L. (Guava) was (4.6 pupils / fruit) and (53.3 pupils / Kg). It was found that the biometric parameters of Psidium guajava L. fruits act on the abundance and diversity of fruit flies in the city.